Identification of a nth-Like Gene Encoding an Endonuclease III in Campylobacter jejuni - Dai, Lei; Xia, Jing; Sahin, Orhan; Zhang, Qijing (Frontiers in Microbiology, 2019)
Abstract: Campylobacter jejuni is a leading cause of foodborne illnesses worldwide. As a microaerobic pathogen, C. jejuni is subjected to DNA damages caused by various stresses such as reactive oxygen species (ROS) and UV radiations. The base excision repair (BER) system plays an important role in preventing mutations associated with oxidative DNA damage, but the system remains poorly characterized in Campylobacter. In this study, a BER homolog encoded by cj0595c (named nth) in C. jejuni was analyzed for endonuclease III activity and for its role in maintaining genomic stability. It was found that inactivation of nth resulted in elevated frequencies of spontaneous fluoroquinolone-resistant (FQR) and oxidative stress resistant (OXR) mutants compared with the wild-type strain in C. jejuni. Sequencing analysis of the FQR and OXR mutants revealed that the elevated mutation rates were associated with C→T or G→A transition in gyrA (FQR mutants) or perR (for OXR mutants). In an in vitro assay, purified recombinant C. jejuni Nth protein demonstrated endonuclease III activity that recognized and excised the thymine glycol (Tg) base from double stranded DNA. These findings indicate that Nth functions as a BER repair enzyme in C. jejuni and is important for repairing of DNA damages, protecting the bacteria from stresses encountered within a host and in the environment.